THE SYNTHESIS AND REACTIONS OF A-RING AROMATIC STEROID COMPLEXES OF MANGANESE TRICARBONYL - WOO, K; CARPENTER, GB; SWEIGART, DA (ELSEVIER SCIENCE SA, 1994)
Treatment of the A-ring aromatic steroids estrone 3-methyl ether and beta-estradiol 3,17-dimethyl ether with Mn(CO)5+BF4- in CH2Cl2 yields the corresponding [(steroid)Mn(CO)3]BF4 salts 1 and 2 as mixtures of a and beta isomers. The X-ray structure of [(estrone 3-methyl ether)Mn(CO)3]BF4 . CH2Cl2 (1) having the Mn(CO)3 moiety on the alpha side of the steroid is reported: space group P2(1) with a=10.3958(9), b=10.9020(6), c=12.6848(9) angstrom, beta=111.857(6)-degrees, Z-2, V=1334.3(2) angstrom3, rho(calc)=1.481 cm-3, R=0.0508, and wR=0.0635. The molecule has the traditional 'piano stool' structure with a planar arene ring and linear Mn-C-O linkages. The nucleophiles NaBH4 and LiCH2C(O)CMe3 add to [(beta-estradiol 3,17-dimethyl ether)Mn(CO)3]BF4 (2) in high yield to give the corresponding alpha- and beta-cyclohexadienyl manganese tricarbonyl complexes (3). The nucleophiles add meta to the arene -OMe substituent and e-w to the metal. The alpha and beta isomers of 3 were separated by fractional crystallization and the X-ray structure of the beta isomer with an ew-CH2C(O)CMe3 substituent is reported (complex 4): space group P2(1)2(1)2(1) with a=7.5154(8), b=15.160(2), c=25.230(3) angstrom, Z=4, V=2874.4(5) angstrom3, rho(calc)=1.244 g cm-3, R=0.0529 and wR2=0.1176. The molecule 4 has a planar set of dienyl carbon atoms with the saturated C(l) carbon being 0.592 A out of the plane away from the metal. The results suggest that the manganese-mediated functionalization of aromatic steroids is a viable synthetic procedure with a range of nucleophiles of varying strengths.
Keywords: DOUBLE NUCLEOPHILIC-ADDITION; COORDINATED CYCLOHEXADIENYL; ELECTROPHILIC REACTIVITY; ESTRADIOL DERIVATIVES; BETA-DIASTEREOISOMERS; FORMAL SYNTHESIS; = C5ME5; ARENE; DIFFERENTIATION; CATIONS